The pearl [compact disc, unabridged] - Steinbeck, John, 1902-1968 (Penguin Audio, 1993)
"[R]etells an old Mexican folk tale: the story of the great pearl, how it was found, and how it was lost. For the diver Kino, finding a magnificent pearl means the promise of a better life for his impoverished family. His dream blinds him to the greed and suspicions the pearl arouses in him and his neighbors, and even his loving wife cannot temper his obsession or stem the events leading to the tragedy" -- from publisher's web site.